Neuroinformatika a sdílení dat z lékařských zobrazovacích systémů - Klimek, Martin; Schwarz, Daniel (International Society for Science and Engineering, o.s., 2011)
This article discuses the matter of medical imagining data sharing and storing. Administrative and informatics aspects of medical imaging systems data in multicentric studies including MRI brain images and technical design of a web-based application for image data sharing including a web interface suitable for manipulation with the image data stored in a database are also dealt in this paper.

Článek se zabývá problematikou skladování a sdílení primárních neurozobrazovacích dat. Článek obsahuje mj. organizační a informatické aspekty sdílení obrazových dat v multicentrických studiích s obrazy mozku z magnetické rezo-nance. Součástí článku je i technické řešení sdílení dat včetně návrhu webového rozhraní pro práci s obrazovými daty v databázi.
Neuroinformatics and sharing data from medical imaging systems
Keywords: Elektrorevue; multicentrický sběr dat; klinické registry; anonymizace; Elektrorevue; multicentric data collection; clinical registry/registries; anonymization